Two items on the Hamilton Depression rating scale are effective predictors of remission: Comparison of selective serotonin reuptake inhibitors with the combined serotonin/norepinephrine reuptake inhibitor, venlafaxine - Silverstone, P. H.; Entsuah, Richard; Hackett, D. (International Clinical Psychopharmacology, 2002)
Investigated whether the responses on 2 items of the Hamilton Depression (HAM-D) scale, Depressed Mood and Psychic Anxiety, were predictive of remission of depression in placebo-controlled studies following treatment with venlafaxine or selective serotonin reuptake inhibitors (SSRIs). Data from 8 active- and placebo-controlled studies consisting of 2,027 subjects (Ss) who met the DSM-III-R/-IV criteria for major depressive disorder were analyzed. Three treatment groups were compared: venlafaxine (n=843), SSRI (n=743) and placebo (n=441). Treatment duration was 6-8 wks. Ss who scored zero on the depressed mood and the psychic anxiety items of the HAM-D₁₇ scale were designated as responders. These 2 scores were also combined to create an Absence of Depressive and Anxious Mood (ADAM) score. Between-group rate comparisons in outcome measures were carried out using Fisher's exact test and logistic regression models. Venlafaxine treatment improved depressed mood, psychic anxiety and ADAM scores after 2 wks with greater efficacy than treatment with SSRls or placebo. ADAM scores could also predict the odds ratio of a patient achieving a clinical remission. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Adolescent; Adult; Affect; Aged; Aged, 80 and over; Anxiety; Cyclohexanols; Depressed Mood; Depression (Emotion); Depressive Disorder; Drug Therapy; Female; Hamilton Depression Rating Scale; Humans; Major Depression; Male; Middle Aged; Norepinephrine; Placebos; Prediction; Predictive Value of Tests; Psychic Anxiety; Rating Scales; Remission (Disorders); Reuptake; SSRI; Serotonin Norepinephrine Reuptake Inhibitors; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Severity of Illness Index; Treatment Outcome; Venlafaxine; Venlafaxine Hydrochloride; major depression; prediction; remission; selective serotonin reuptake inhibitors; venlafaxine